Ancestral Veneration as a Metaphysical Issue in Yòrùbá Culture: Exploring the Spiritual Agency of Social Reconstruction in a Glocal Context - ADESANYA, Oreoluwa Idris (Àgídìgbo: ABUAD Journal of the Humanities, 2025)
Africans are in the habit of venerating the dead among them who qualify as ancestors. The practice of ancestral veneration in Africa, particularly amongst the Yòrùbá people of West Africa, is premised on their belief in continual existence after death. The supposition is that the dead, who have now become ancestors, play active roles in their activities, in the plight of their children and grandchildren and their lives entirely. The ancestors are believed to possess the ability to influence either positively or negatively the fortune of the living. Belief in the existence of ancestors amongst Africans is paramount in African traditional religious belief systems. The ancestors are taken to be intermediaries between the living, the divinities and the Supreme Being. Ancestors therefore occupy an important place in African, particularly Yòrùbá ontology. Communion with ancestors therefore takes the form of veneration, in which the people honour, respect and look after them in their afterlives as well as possibly seek their guidance for the living descendants. Among the Yòrùbá people, ancestral veneration takes various forms as being evident in their traditional practices. The Yòrùbá have requirements for the conferment of ancestor-hood on a deceased soul, and as such not everyone who dies becomes an ancestor in Yòrùbá ontology. The task of this paper is to interrogate the practice of ancestral veneration as a metaphysical issue that is evident among the Yòrùbá people of Africa, while also delving into the discussion of the basic requirements for ancestor-hood amongst the Yòrùbá. This paper presents ancestors in Yòrùbá culture as spiritual agents of establishing social order, based on the belief in their continual relevance in the physical world. The role of ancestors as spiritual agents of social reconstruction will also be interrogated against emergent and dominant forces, such as globalisation, using the framework of glocalisation.